Penerapan Metode Certainty Factor Untuk Sistem Pakar Dalam Mengidentifikasi Jenis Kerusakan Yang Terjadi Pada Radar Aaws Di Kantor BMKG Medan - Damayanti, Damayanti (Jurnal Sains dan Teknologi Informasi, 2022)
AAWS Radar (Automatic Agroclimate and Weather Station) can also be called automatic agro-climate and weather monitoring post is a tool and installed by BMKG to monitor weather and climate elements automatically and directed to the agricultural sector. With this tool, of course, it can really help BMKG in observing the weather which is certainly useful for agencies from the agricultural sector. Although this radar is very helpful, but when it has been used for a long time it will definitely be damaged. Research with the title "Application of Certainty Factor Methods for Expert Systems in Identifying Types of Damage that Occurs on the AAWS Radar at the BMKG Medan Office". Has a problem formulation such as what damage often occurs on the AAWS radar. The purpose of this study is to determine the cause of damage to the AAWS radar. This research uses direct observation and interview methods with management and experts from the company. The source of the data used is data that will be provided directly from the company where the research is carried out. The data were analyzed using the Expert System with the Certainty Factor method. The theoretical basis used in this research is to describe the theories related to the Expert System and the Certainty Factor Method. Based on the research that has been done, it is concluded that BMKG pays great attention to every existing tool, one of which is the AAWS radar. Because this tool is very influential in the agricultural sector